A novel strategy to identify analytical markers of Cerebralcare Granule for quality assessment by ultra-high performance chromatography and chemometric analysis1. Issue 15 (7th August 2015) - Li, Xiao-wen; Tong, Ling; Li, Dong-xiang; Sun, Wan-yang; Sun, Guo-xiang
<x xml:space="preserve">Abstract</x> Selecting appropriate analytical markers of botanical drugs is a critical step in quality control.